2022
DOI: 10.3390/cancers14092109
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Profiling Predicts Nodal Status and Disease Recurrence in Patients Treated with Curative Intent for Colorectal Cancer

Abstract: Background: Approximately one-third of colorectal cancer (CRC) patients will suffer recurrence. MiRNAs are small non-coding RNAs that play important roles in gene expression. We aimed to correlate miRNA expression with aggressive clinicopathological characteristics and survival outcomes in CRC. Methods: Tumour samples were extracted from 74 CRC patients. MiRNAs were quantified using real-time reverse transcriptase polymerase chain reaction. Descriptive statistics and Cox regression analyses were performed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…MicroRNAs act at a post-transcriptional level by binding to messenger RNA (mRNA) and influencing protein synthesis at a cellular level [ 7 ]. Recent data has illustrated the relevance of miRNA measurement to predict response to therapeutic strategies [ 7 , 8 , 9 , 10 ], enhancing cancer diagnostics [ 11 , 12 ], and predicting long-term outcomes for those diagnosed with malignancy [ 13 , 14 ]. In combination, these favourable characteristics illustrate the candidacy of miRNAs as biomarkers in the context of breast cancer research [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs act at a post-transcriptional level by binding to messenger RNA (mRNA) and influencing protein synthesis at a cellular level [ 7 ]. Recent data has illustrated the relevance of miRNA measurement to predict response to therapeutic strategies [ 7 , 8 , 9 , 10 ], enhancing cancer diagnostics [ 11 , 12 ], and predicting long-term outcomes for those diagnosed with malignancy [ 13 , 14 ]. In combination, these favourable characteristics illustrate the candidacy of miRNAs as biomarkers in the context of breast cancer research [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even alone, they possess the characteristics of biomarkers required to stratify different sub-groups of patients based on their microsatellite instability (MSI) status 17 . Also, CRC patients with positive lymphatic invasion have been presented to have aberrant expression of miRNA21 and miRNA135b 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the seminal work of these authors, the role of miRNAs in breast cancer has been further elucidated. For example, previous authors have demonstrated the capabilities of miRNAs to predict breast cancer hormone receptor status, others have evaluated the role of miRNAs as therapeutic options in cancer [ 19 , 20 , 21 , 22 ], and several previous reports have correlated miRNA expression profiles with long-term survival outcomes in malignancy [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%